2019
DOI: 10.1515/ijamh-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis of lower limbs in adolescents: a study in a tertiary hospital

Abstract: BackgroundVenous thromboembolism (VTE) – which includes deep venous thrombosis (DVT) and pulmonary embolism (PE) – has been increasingly recognized in the pediatric population. The estimated incidence is 0.07–0.14 cases per 10,000 children. Most cases are associated with two or more risk factors. Medium and long-term complications include recurrence and post-thrombotic syndrome (PTS).ObjectiveTo characterize the adolescent population with the diagnosis of DVT of lower limbs in a tertiary hospital, regarding it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A study has shown that the annual incidence of DVT in cancer patients is much higher than that in healthy people (4). DVT mostly occurs in the lower extremities, especially the lower legs (5). It has been found that the destruction of the homeostatic equilibrium of the coagulation and fibrinolytic systems, caused by vascular endothelial injury and increased inflammatory response, can easily lead to DVT (6).…”
Section: Original Articlementioning
confidence: 99%
“…A study has shown that the annual incidence of DVT in cancer patients is much higher than that in healthy people (4). DVT mostly occurs in the lower extremities, especially the lower legs (5). It has been found that the destruction of the homeostatic equilibrium of the coagulation and fibrinolytic systems, caused by vascular endothelial injury and increased inflammatory response, can easily lead to DVT (6).…”
Section: Original Articlementioning
confidence: 99%
“…Several risk factors, both inherited and acquired, have been examined and linked to venous thrombotic events, and their discovery can help improve diagnostic methods and, more critically, thrombotic event prevention. Deep vein thromboembolism does not have a gender preference, but men seem to be more likely to have recurring incidences and the risk rises as people get older, partly due to an increase in the prevalence of medical disorders and other risk factors in the aged population (Faria, Antunes, H., Pontes, Antunes, A., Martins & Carvalho 2019). Both smoking and obesity have been linked to an increased risk of deep vein thromboembolism.…”
Section: Introductionmentioning
confidence: 99%